2023
DOI: 10.3390/ijms241713513
|View full text |Cite
|
Sign up to set email alerts
|

Common miRNAs of Osteoporosis and Fibromyalgia: A Review

Soline Philippe,
Marine Delay,
Nicolas Macian
et al.

Abstract: A significant clinical association between osteoporosis (OP) and fibromyalgia (FM) has been shown in the literature. Given the need for specific biomarkers to improve OP and FM management, common miRNAs might provide promising tracks for future prevention and treatment. The aim of this review is to identify miRNAs described in OP and FM, and dysregulated in the same direction in both pathologies. The PubMed database was searched until June 2023, with a clear mention of OP, FM, and miRNA expression. Clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 153 publications
(149 reference statements)
0
1
0
Order By: Relevance
“… 1 Changes in miR levels have been associated with phenotypic changes with aging and diseases, including osteoporosis. 2 Among the most commonly studied miRs, miR21, a pro-survival and oncogenic miR, has been shown to directly regulate osteoblast and osteoclast differentiation and function. 3 In addition, we have shown that miR21 is reduced with Cx43 deficiency and aging in female mice, and that its deletion from osteocytic cells results in a sex-dimorphic effect on the skeleton.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Changes in miR levels have been associated with phenotypic changes with aging and diseases, including osteoporosis. 2 Among the most commonly studied miRs, miR21, a pro-survival and oncogenic miR, has been shown to directly regulate osteoblast and osteoclast differentiation and function. 3 In addition, we have shown that miR21 is reduced with Cx43 deficiency and aging in female mice, and that its deletion from osteocytic cells results in a sex-dimorphic effect on the skeleton.…”
Section: Introductionmentioning
confidence: 99%